2021
DOI: 10.1007/s00415-021-10526-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of the enzyme replacement therapy in patients with late-onset Pompe disease: a systematic review and a meta-analysis

Abstract: In patients with late-onset Pompe disease (LOPD), the efficacy of the enzyme replacement therapy (ERT) with recombinant human alpha-glucosidase (rhGAA) is difficult to evaluate, due to the clinical heterogeneity and the small sample sizes in published studies. Therefore, we conduct a systematic literature review and meta-analysis of the literature to evaluate the efficacy of ERT in LOPD patients considering the walking distance, respiratory function and muscle strength. Particularly, six-minute walk test (6MWT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…These results were confirmed in a recent meta-analysis including 413 aLOPD. 10 Surprisingly, the effectiveness of muscle strengthening of aLOPD has received little attention in the literature. 9,23,24 Two studies showed strength gains after muscle strengthening interventions in lower limb muscles.…”
Section: Discussionmentioning
confidence: 99%
“…These results were confirmed in a recent meta-analysis including 413 aLOPD. 10 Surprisingly, the effectiveness of muscle strengthening of aLOPD has received little attention in the literature. 9,23,24 Two studies showed strength gains after muscle strengthening interventions in lower limb muscles.…”
Section: Discussionmentioning
confidence: 99%
“…6MWT has long been an easy and comprehensive tool to evaluate the general functional capacity of patients with chronic pulmonary, cardiac, or neuromuscular disease [ 39 ]. It is widely used in patients with Pompe disease and mucopolysaccharidosis (MPS) as a useful clinical endpoint of ERT treatment response [ [40] , [41] , [42] ]. It has also been investigated in a few patients with ASMD.…”
Section: Discussionmentioning
confidence: 99%
“…in 50% of patients (Supplementary Figure S3), especially in those with longer disease duration. This improvement in motor response peaking 1-3 years after the start of ERT, followed by stabilization, is common to most studies (Anderson et al, 2014;Kuperus et al, 2017;Schoser et al, 2017), and confirmed by recent reviews (Dornelles et al, 2021;Sarah et al, 2021). A recent review (Berli et al, 2021) failed to detect significant changes in FVC, that remained stable during a follow-up ranging 6 months to 7 years in different studies.…”
Section: Main Motor and Respiratory Outcomes: 6mwt And Fvcmentioning
confidence: 64%